Renewable Energy: Thin Film Co3O4/TiO2 Heterojunction Solar Cells (Adv. Energy Mater. 1/2015). Issue 1 (January 2015) - Kupfer, Benjamin; Majhi, Koushik; Keller, David A.; Bouhadana, Yaniv; Rühle, Sven; Barad, Hannah Noa; Anderson, Assaf Y.; Zaban, Arie
<x xml:space="preserve">Abstract</x> In article number 1401007, Assaf Y. Anderson, Arie Zaban, and co‐workers use combinatorial material science to develop an all oxide photovoltaic (PV) heterojunction consisting of anatase TiO2 and spinel Co3O4. This finding is a critical milestone in ongoing research towards all‐oxide photovoltaics, which hold the potential to become the most ecofriendly and cost‐effective renewable energy source. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>